Challenges for sustainable maize production of smallholder farmers in sub-Saharan Africa. (September 2021) - Cairns, Jill E.; Chamberlin, Jordan; Rutsaert, Pieter; Voss, Rachel C.; Ndhlela, Thokozile; Magorokosho, Cosmos
Abstract: Maize production must increase three-fold in sub-Saharan Africa to meet the needs of future generations. Sustainably increasing maize production will require a portfolio of complementary technologies and policies. In this review we highlight four challenges to achieve this improvement. Improved nutritional density of maize in farmers' fields and increased adoption of new varieties and faster varietal replacement. Increased fertilizer use should increase maize yields but there is increasing evidence that low and variable returns on investment can limit uptake. Finally, adoption of new technologies is not uniform, with lower rates of adoption by female farmers. Without addressing gender specific challenges to adoption, technologies will never achieve their desired impacts. Given the scope of the challenge, strategies to improve maize productivity must overcome these constraints as part of an integrative approach. Graphical abstract: Image 1 Highlights: Biofortification targets need to consider soil fertility gradients. Barriers exist for business to successfully push new products onto the market. Inclusion of consumer preferred traits may increase adoption. Attainable yield of new varieties depends on complementary management practices. Technology adoption constraints are context-specific and gendered.